Parallel Diplomacy of Bali and Hainan in A Cultural Economic Perspective - Jernihati, Amanda; Alam, Gilang Nur; Dermawan, Windy (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2025)
This article investigates the parallelism between the Bali Provincial Government and the Indonesian Central Government in the context of parallel diplomacy through the sister province program between Bali and Hainan Province. This research mainly focuses on the tourism and cultural sectors, analyzed through a cultural economic perspective, where culture is commercialized with certain modifications. However, the Bali Provincial Government, through the Cultural Office, does not prohibit these modifications as long as they adhere to cultural norms and ethics, distinguishing between elements that can be commercialized and those that cannot. This study employs a qualitative method, sourcing data through field studies and literature reviews. The findings indicate harmony and alignment in the relationship between the regional and central governments, reflecting mutually supportive collaboration without significant conflict. The study suggests that this synergy should be continuously strengthened to support the sustainability of cultural diplomacy and cultural economy internationally.